1980
DOI: 10.1051/jphyscol:1980638
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation dynamics in alkali halide single crystals investigated by nuclear spin relaxation measurements

Abstract: Résumé. -La résonance magnétique nucléaire est appliquée à l'étude de la variation de la vitesse des dislocations avec la contrainte de compression appliquée dans des cristaux d'halogénures alcalins. T lp a été mesurée en fonction du taux s de la déformation plastique. La route moyenne des dislocations mobiles a été déterminée. Nous indiquons les résultats des expériences sur de différents noyaux, sur de différentes orientations des cristaux et sur des températures différentes.Abstract. -Dislocations moving at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Results are described in detail in ref 79. This has indeed been demonstrated: bulk viscosity can be directly calculated from species exchange rates measured by NMR. 79 The exchange among Si sites is mirrored by that among 0 sites: 170 NMR has shown that bridging and nonbridging oxygens interchange at rates comparable to that of the Si sites.89 This kind of study has been extended to temperatures just above T" by two dimensional exchange spectroscopy. 90 This kina of structural exchange is in marked contrast to the behavior of a mixture of molten alkali nitrate and sulfate, where no exchange among the oxygens bound to these molecular anions was observed.1 A few relaxation time studies of network forming species in oxide glasses and liquids have been made, with some early high-temperature relaxation time results, on UB in B203.91'92 "Si data in glassy and liquid silicates have proven difficult to understand in complete detail, in part because of the sensitivity to paramagnetic impurities.79,88 However, relaxation mechanisms change abruptly near the bulk glass transition temperature, probably because of the structural mobility that begins at that point.79,88 Apparent activation energies in the liquid region are similar to those for viscosity.…”
Section: B Glasses and Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results are described in detail in ref 79. This has indeed been demonstrated: bulk viscosity can be directly calculated from species exchange rates measured by NMR. 79 The exchange among Si sites is mirrored by that among 0 sites: 170 NMR has shown that bridging and nonbridging oxygens interchange at rates comparable to that of the Si sites.89 This kind of study has been extended to temperatures just above T" by two dimensional exchange spectroscopy. 90 This kina of structural exchange is in marked contrast to the behavior of a mixture of molten alkali nitrate and sulfate, where no exchange among the oxygens bound to these molecular anions was observed.1 A few relaxation time studies of network forming species in oxide glasses and liquids have been made, with some early high-temperature relaxation time results, on UB in B203.91'92 "Si data in glassy and liquid silicates have proven difficult to understand in complete detail, in part because of the sensitivity to paramagnetic impurities.79,88 However, relaxation mechanisms change abruptly near the bulk glass transition temperature, probably because of the structural mobility that begins at that point.79,88 Apparent activation energies in the liquid region are similar to those for viscosity.…”
Section: B Glasses and Liquidsmentioning
confidence: 99%
“…Oxide anion conducting ceramics are especially interesting as high-temperature solid electrolytes in oxygen pressure sensors. 170 NMR generally requires the use of isotopically enriched materials because of the low natural abundance and Larmor frequency, but a few studies have been made at high temperature. Conduction in Ce02, for example, is controlled by the abundance of defects generated by doping with a lower valence oxide such as Y203.…”
Section: B Glasses and Liquidsmentioning
confidence: 99%
See 1 more Smart Citation